A New Hybrid Prediction Approach For Enhance Prediction Accuracy of Complex Data (International Journal of Engineering and Computer Science, 2018)
Over past few decades a lot of approaches have introduced for data prediction practice and many of researchers are continuously introducing their unique ideas on a daily basis for enhancing the power of prediction system in different areas but each and every approach has its own limitation. One of the most limitations of existing prediction approaches is that they are designed with the strength of a single classification technique and are not enough to handle different types of data efficiently thus the cost of system is high and field still lacks with high rate of prediction accuracy. This dilemma of existing prediction systems has consider into this paper with proposing  an effective and efficient data prediction system that enhances data prediction accuracy  in a significant way